2009
DOI: 10.1007/s00404-009-1308-5
|View full text |Cite
|
Sign up to set email alerts
|

GnRH analogs do not protect ovaries from chemotherapy-induced ultrastructural injury in Hodgkin’s lymphoma patients

Abstract: The results of this study demonstrate ultrastructural ovarian damage in Hodgkin's lymphoma patients irrespective of GnRHa co-treatment. These findings do not support previous studies, showing GnRHa to protect ovarian function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Although several investigators have demonstrated that GnRH-a may inhibit chemotherapy-induced ovarian follicular depletion in rats and rhesus monkeys, some investigators still consider it to be an equivocal and controversial issue in humans [14,[39][40][41][42][43][44]. The only prospective randomized study with histological counting of follicles [38] has shown that in rhesus monkeys, GnRH-a protected the ovary against cyclophosphamide-induced damage by significantly decreasing the number of primordial and primary follicles lost during the chemotherapeutic insult.…”
Section: Discussion: the Arguments 'For And Against' Gnrh-a Co-treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Although several investigators have demonstrated that GnRH-a may inhibit chemotherapy-induced ovarian follicular depletion in rats and rhesus monkeys, some investigators still consider it to be an equivocal and controversial issue in humans [14,[39][40][41][42][43][44]. The only prospective randomized study with histological counting of follicles [38] has shown that in rhesus monkeys, GnRH-a protected the ovary against cyclophosphamide-induced damage by significantly decreasing the number of primordial and primary follicles lost during the chemotherapeutic insult.…”
Section: Discussion: the Arguments 'For And Against' Gnrh-a Co-treatmentmentioning
confidence: 94%
“…However, there are also seven studies claiming that GnRH-a is not helpful for the preservation of ovarian function [9,14,[39][40][41][42][43][44], which were brought up by the opponents to this treatment as an evidence against its use as a co-treatment. Waxman et al found in 1987 that four out of eight female patients treated with Buserelin GnRH-a in parallel to chemotherapy suffered POF (50%) versus six of the nine patients in the control group (66.7%) [40].…”
Section: Discussion: the Arguments 'For And Against' Gnrh-a Co-treatmentmentioning
confidence: 95%
“…47,48 Two other studies (the most recent was conducted by the German group) that randomized oral contraceptives and GnRH in patients treated with escalated BEACOPP were unable to find evidence of any efficacy of GnRH which did not improve the hormone assays. 49,50 Analogs of LHRH are, therefore, not recommended in the absence of studies demonstrating their effectiveness. For women who experience premature menopause, hormone replacement therapy may reduce the risks of estrogen deficiency, such as osteoporosis.…”
Section: Different Fertility Preservation Methodsmentioning
confidence: 99%
“…An argument against GnRHa use [18] claims that prepubertal children, whose hypogonadotropic milieu is simulated by the GnRHa, receiving high-dose chemotherapy given before hematopoietic stem cell transplantation still suffer from ovarian failure. Remérand et al [19] have described four spontaneous pregnancies and successful deliveries in a patient after prepubertal high-dose busulfan and cyclophosphamide conditioning and bone marrow transplantation (BMT), demonstrating that successful pregnancies may occur in patients undergoing prepubertal BMT.…”
Section: Discussionmentioning
confidence: 99%